A2 + b2 + c2 is equal to?​

Answer: (a + b + c)² = a² + b² + c² + 2 (ab + bc + ca)

We can solve the equation by considering (a + b + c)2 into (a + b + c)(a + b + c)

(a + b + c)(a + b + c) = a × (a + b + c) + b × (a + b + c) + c × (a + b + c)

(a + b + c)(a + b + c) = a2 + ab + ac + ba + b2 + bc + ca + cb + c2

(a + b + c)(a + b + c) = a2 + b2 + c2 + 2ab + 2bc + 2ca

(a + b + c)² = a2 + b2 + c2 + 2 (ab + bc + ca)

Leave a Comment

Your email address will not be published. Required fields are marked *

BOOK

Free Class